Study the Phenolic Compounds and Antioxidant Activity of the Extract Lily (Lilium ledebourii (Baker) Boiss) - Shekoofeh Shokrollahi; GholamAli Heshmati; Hamed YosefZadeh (Fasa University of Medical Sciences, 2018)
Background & Objective: Lilium ledebourii (Baker) Boiss, is the only national and natural heritage of Iran, which grows in mountainous regions of Hyrcanian forests with limited distribution that many ecological, ornamental and medicinal aspects of this plant has not been studied yet. Material & Methods: Ethanolic extract was prepared by maceration method. Then, total phenol and total flavonoids of ethanolic extracts were respectively performed by the Folin- Ciocalteu and AlCl3 method. Antioxidant activity was measured by scavenging free radicals of DPPH. Statistical analysis of the data was performed by ANOVA (Analysis of Variance) and Duncan Test to compare the means. Results: The total phenols of Lily shoots was between 59/6 ± 65/43 and 21/9 ± 14/66 and its antioxidant activity was between 51 to 90 percent at four habitats, The highest and lowest amount of total phenols and antioxidant activity of Lily shoots obtained from Kelardasht (maximum altitude) and Rostam Abad (minimum altitude). The total flavonoid were reported between 91/7 ± 41/33 mg GAE g-1 and 21/1 ± 72/43 mg QUE g-1. The highest and lowest content of Total flavonoid were respectively observed in Asalem and Namin. Conclusion: The results showed that the antioxidant capacity of Lily is relatively high compared to other medicinal plants, also antioxidant activity of the Lily extract is variable in different sites and significantly affected by habitat altitude.